Forenzična genetika - Zupanič-Pajnič, Irena (Medicinski razgledi, 2011)
This article describes forensic genetics investigations performed in Slovenia and abroad. At the Molecular Genetic Laboratory of the Institute of Forensic Medicine, close and distinct kinship analyses are performed, biological stainsare analyzed in casework, and human skeletal remains are identified fromforensic investigations, World War II mass graves and archeological sites.Identification of tissue samples is performed in clinical examinations whenever a suspicion of exchange appears. Furthermore, hematopoietic ceH chimerism is monitored after bone marrow transplantations, and zygosity in twins is determined before transplantations. The paper describes variable genetic markers used in forensic genetics. Whenever nuclear autosomal and Y chromosome Short Tandem Repeat loci are used, length polymorphisms are traced.In the variable control region of the mitochondrial DNA, sequence polymorphisms are analyzed. In the paper, the most famous genetics investigations for the reconstruction of historical cases are presented, some mass disaster victimidentifications are listed, and some identifications of notabilities of our past are described.
Keywords: Forensic Medicine; Rodovnik; Sodna medicina; Genetics, Medical; DNA mitohondrijska; Dna, Mitochondrial; Microsatellite Repeats; Genetika medicinska; Pedigree; Mikrosatelitne ponovitve; Polimorfizem (genetika); Karyotyping; Polymorphism (Genetics); Ponovljiva zaporedja nukleinske kisline; Kariotip, določanje; Dna Probes, Hla; medicinska genetika; Y Chromosome; Repetitive Sequences, Nucleic Acid; forenzične preiskave; DNA sonde, HLA; molekularna genetika; Y kromosom